Statistical quark model for the nucleon structure function - Mirez, Carlos [UNESP]; Tomio, Lauro [UNESP]; Trevisan, Luis A.; Frederico, Tobias (My University, 2009)
A statistical quark model, with quark energy levels given by a central linear confining potential is used to obtain the light sea-quark asymmetry, d̄/ū, and also for the ratio d/u, inside the nucleon. After adjusting a temperature parameter by the Gottfried sum rule violation, and chemical potentials by the valence up and down quark normalizations, the results are compared with experimental data available. © 2009 American Institute of Physics.
Keywords: Flavor symmetries; Quark models; Structure function